Does prospective payment increase hospital (in)efficiency? Evidence from the Swiss hospital sector - Philippe K. Widmer (University of Zurich, Department of Economics, 2011)
Several European countries have followed the United States in introducing prospective payment for hospitals with the expectation of achieving cost efficiency gains. This article examines whether theoretical expectations of cost efficiency gains can be empirically confirmed. In contrast to previous studies, the analysis of Switzerland provides a comparison of a retrospective per diem payment system with a prospective global budget and a payment per patient case system. Using a sample of approximately 90 public financed Swiss hospitals during the years 2004 to 2009 and Bayesian inference of a standard and a random parameter frontier model, cost efficiency gains are found, particularly with a payment per patient case system. Payment systems designed to put hospitals at operating risk are more effective than retrospective payment systems. However, hospitals are heterogeneous with respect to their production technologies, making a random parameter frontier model the superior specification for Switzerland.
Keywords: C11; C23; D24; I18; 330; hospital inefficiency; prospective payment system; Bayesian inference; stochastic frontier analysis; Gesundheitsversorgung; Krankenhaus; Wirtschaftliche Effizienz; Schätzung; Schweiz